2009
DOI: 10.1186/1742-2094-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the complement regulatory molecule CD59a leads to exacerbated neuropathology after traumatic brain injury in mice

Abstract: Background: Complement represents a crucial mediator of neuroinflammation and neurodegeneration after traumatic brain injury. The role of the terminal complement activation pathway, leading to generation of the membrane attack complex (MAC), has not been thoroughly investigated. CD59 is the major regulator of MAC formation and represents an essential protector from homologous cell injury after complement activation in the injured brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…Other groups have shown that MAC is a potent inducer of tissue injury also in the CNS, inducing upregulation of adhesion molecules and leukocyte infiltration (36), evoking epileptic seizures and neuronal cell death (37) in healthy rats, and contributing to demyelination and axonal injury in the EAE model of multiple sclerosis (24). Studies using mice deleted of the CD59a gene, the intrinsic regulator of MAC assembly, showed that CD59a-deficient mice are more susceptible to peripheral nerve trauma (16), ischemia/reperfusion injuries (38), EAE-induced demyelination and axonal injury (39), as well as neuropathology and neurologic impairment after closed head injury (8). Taken together, these studies support a detrimental role of MAC in the brain and point to a potential therapeutic effect of MAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other groups have shown that MAC is a potent inducer of tissue injury also in the CNS, inducing upregulation of adhesion molecules and leukocyte infiltration (36), evoking epileptic seizures and neuronal cell death (37) in healthy rats, and contributing to demyelination and axonal injury in the EAE model of multiple sclerosis (24). Studies using mice deleted of the CD59a gene, the intrinsic regulator of MAC assembly, showed that CD59a-deficient mice are more susceptible to peripheral nerve trauma (16), ischemia/reperfusion injuries (38), EAE-induced demyelination and axonal injury (39), as well as neuropathology and neurologic impairment after closed head injury (8). Taken together, these studies support a detrimental role of MAC in the brain and point to a potential therapeutic effect of MAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that genetic deletion of C6, a necessary component of the MAC, is neuroprotective after peripheral nerve trauma (15,17). Another study showed that deletion of CD59a, the major regulator of MAC formation in mice, aggravates secondary neuronal cell death after brain trauma, suggesting a key role for MAC in the pathophysiology of TBI (8). However, the effects of specific inhibition of MAC formation have never been tested in TBI.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Further, mice treated with C1 inhibitor, a serine protease inhibitor of the classical and lectin complement pathways, showed reduced neurobehavioural deficits and contusion volume after controlled cortical impact brain injury [63]. Involvement of the terminal complement pathway in experimental TBI has been proven because mice lacking the sole membrane bound regulator of the MAC, CD59a, display increased neuronal cell death and brain tissue destruction compared to CD59a +/+ littermates [64]. Our group has initially shown that MAC is a key component of axonal injury, driving Wallerian degeneration after peripheral nerve trauma, and we have also recently proven that exogenous blockers of MAC assembly are neuroprotective in an experimental mouse model of severe closed head injury (unpublished observations).…”
Section: Microscopic Neuropathological Changesmentioning
confidence: 99%
“…In addition, neuronal cell death was determined in brain tissue cryosections 10-lm thick, using the terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) method (Fluorescein In Situ Cell Death Detection Kit; Roche, Mannheim, Germany), as previously described (Harhausen et al, 2010;Stahel et al, 2009). Briefly, the cerebellum of the frozen brains was cut off, the brain was mounted on a removable chuck on the cryostat, and the brain was covered with OCT (Tissue Tek; Sakura Finetek, Torrance, CA).…”
Section: Tunel and Immunohistochemistrymentioning
confidence: 99%